Hoist your sails and run - McGrath, Robin (St.John's Newfoundland, 1999)
Knowing of an ancestor's confrontation with a legendary giant squid more than a century ago, Aquin White begins a high school science project on the mysterious creature and soon comes to learn of its importance to his family. Soon Aquin's world is turned upside down when he must come to terms with the ensuing death of his grandfather, his changing relationship with his best friend Emma and the fact that he may have to leave Newfoundland forever.